IMPLEMENTASI PASAL 5 AYAT (7) PERATURAN DAERAH KOTA PEKANBARU NOMOR 3 TAHUN 2002 TENTANG HIBURAN UMUM DI KOTA PEKANBARU - Mhd Ichsan; Dessy Artina; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
One of the policies that regulate entertainment in Pekanbaru City is Regional Regulation No. 3 of 2002 concerning Public Entertainment in Pekanbaru City. Based on Article 5, paragraph 7, Regional Regulation No. 3 of 2002, it is explained about the operational timing of video games / play stations. This fact can be seen from how the government regulates public entertainment in Pekanbaru City. Types of entertainment regulated in Regional Regulation No. 3 of 2002 in its implementation there are still violations in its implementation. Therefore, it is necessary to study the first stimulant, the implementation of Article 5 paragraph (7) Pekanbaru City Regional Regulation Number 3 of 2002 concerning public entertainment in Pekanbaru City, Second, obstacles in the implementation of Article 5 paragraph (7) Pekanbaru City Regional Regulation Number 3 Year 2002 Regarding public entertainment in Pekanbaru City. Third, the efforts made by the government to curb the operational hours of public entertainment venues for video game rentals / play stations.This research is a sociological legal research, because it is based on field research, namely by collecting data from interviews, questionnaires, and literature reviews that are related to the problems to be studied assisted by primary, secondary and tertiary data. This study uses qualitative data analysis and produces descriptive data.From the results of the research, it is concluded that, first, the implementation of Article 5 paragraph 7 of Pekanbaru City Regional Regulation Number 3 of 2002 concerning Public Entertainment in Pekanbaru City has not been running optimally. Second, lack of understanding and lack of awareness of video games / play station rental owners towards Regional Regulations Number 3 of 2002 concerning Public Entertainment, Lack of control and supervision of Satpol PP Pekanbaru City, Lack of Service Officers, Third, future efforts are to conduct socialization, add personnel in controlling and supervising every video game rental / play station, optimizing supervision and giving strict sanctions video game / play station rental business actors who do not comply with entertainment operating hours. The author's suggestions are, First, Satpol PP of Pekanbaru City is expected to make effective control and cooperate with the Regional Government in increasing peace for the surrounding community, Second, to increase socialization to business actors, Third, to discuss the effectiveness of local regulations regarding video game rentals / play stations.Keywords: Implementation-Regional Regulation-General Entertainment